Can the asymmetry of Okun's law be interpreted from a social perspective? Evidence from the World Bank - Yi, Lin; Kaifeng, Song; Jingbin, Tu; Liangrong, Lai (Frontiers in Public Health, 2022)
Okun's law is demonstrated based on data from the World Development Indicators (WDI) dataset. There is indeed a relationship between unemployment and economic growth, with unemployment negatively affecting economic growth after controlling for the two-way causality problem. This result remains robust after replacing the core explanatory variables. This paper interprets the asymmetry of Okun's law from a social perspective, using alcohol consumption as a mediating variable to measure the harm caused by unemployment to the unemployed. Analysis of the data reveals that alcohol consumption has a mediating effect between unemployment and economic growth. Unemployment increases alcohol consumption, which causes incurable harm to the unemployed. It reduces the willingness and probability of the unemployed to re-employ and further reduces the potential for economic growth. This is why the economic expansion did not lead to employment growth, revealing the asymmetry of Okun's law. The gender-specific heterogeneity analysis found that the impact of unemployment on economic growth did not vary much by gender.